(untitled) (Journal of the College of Basic Education, 2022)
Internal optical loss in a QD laser couples the confined-carrier level occupancy in QDs to the free-carrier density in the OCL. Due to this coupling, which is controlled by the threshold condition, the free-carrier density is increased and more temperature-sensitive, and also the confined-carrier level occupancy becomes temperature-dependent. As a result, the characteristic temperature of a laser is considerably reduced. Carrier-density-dependent internal loss also sets an upper limit for operating temperatures of a QD laser and constrains the shallowest potential well depth and the smallest tolerable size of a QD at which the lasing can be attained. The dependences of the characteristic temperature, maximum operating temperature, and shallowest potential well depth on the parameters of the structure are obtained. At the maximum operating temperature or when any parameter of the structure is equal to its critical tolerable value, the characteristic temperature reduces to zero.